HISTORICAL - CULTURAL VALUE OF STONE - CRAFTING WORKSHOPS FROM THE LATE NEOLITHIC PERIOD IN THE CENTRAL HIGHLANDS - Lê Xuân Hưng (Tạp chí Khoa học Đại học Đà Lạt, 2019)
Studying the remnants of late neolithic stone-crafting workshops in the Central Highlands plays a particularly important role in understanding this region's culture and prehistory. This article is the result of fieldwork carried out at 45 stone processing sites. The relic materials obtained in the fieldwork demonstrate the process of toolmaking, the technical level, and the ability to create cultural value of each ancient residential community. The diverse relic materials allow us to identify the distribution range of the products made in a factory and recognise the exchange relationships among factories, residential units and neighbouring communities.  From the above research results, this article evaluates the outstanding value of the workshops, contributes to a new cultural assessment of the archaeological relics, and provides a scientific basis for administrators to devise solutions to protect and promote this important heritage.